PELAKSANAAN PEMBEBASAN BERSYARAT (PB) BAGI NARAPIDANA MENURUT UNDANG-UNDANG NOMOR 12 TAHUN 1995 DI LEMBAGA PEMASYARAKATAN KELAS I PALEMBANG - Saputra, Jemmi Angga (IBLAM LAW REVIEW, 2022)
The aim of criminal law is correctional, meaning it is a system of treatment of prisoners in Indonesia which is based on the ideology of social integration, therefore the decision of the Minister of Justice of the Republic of Indonesia Number: M.01.PK.0410 of 1999 regulates Assimilation, Conditional Release (PB), Leave for Release ( CMB) and conditional leave. Conditional Release for prisoners must fulfill the requirements and stages of the Process for Proposing Parole. Basically, it absolutely must be implemented in order to fulfill the quality of Parole itself. However, remembering the mandate of the applicable laws and regulations, not only is the quality of conditional release improved, but the quantity also needs to be considered to balance current government policy, namely considering the security approach and treatment approach for prisoners. The problem formulated in this thesis research is: How is conditional release (PB) implemented for prisoners according to Law Number 12 of 1995 in Palembang Class I Prison? What are the factors inhibiting the implementation of parole for prisoners according to Law number 12 of 1995 in Palembang Class I Prison? The research method used in this research is empirical juridical using primary data obtained directly from the field through interviews with related parties and secondary data through literature study. Data analysis was carried out without testing a hypothesis and then a conclusion was drawn deductively. The results of this research are the implementation of conditional release for prisoners according to Law Number. 12 of 1995 in Palembang Class I Prison has not been implemented in accordance with the policies regulated in the regulations of Law Number. 12 of 1995. This is proven by the fact that there are still many mechanisms and procedures that hinder the implementation of conditional release (PB), while the inhibiting factors in the process of granting PB to prisoners according to Law Number 12 of 1995 in Palembang Class I Prison are : Domicile Guarantee Factors, Existence Factors of Litmas or Correctional Centers (Bapas), South Sumatra Kumham Regional Officer Factors, Directorate General of Corrections Officer Factors, Process Factors, Fine Factors, Policy Factors